Comprehensive Intervention Module to Improve Foot Self- Care Knowledge in Patients with Diabetes Mellitus: Módulo de intervención integral para mejorar el conocimiento del autocuidado de los pies en pacientes con diabetes mellitus - Joeliantina, Anita; Norontoko, Dwi Adji; Wuryaningsih, Sri Hardi; Yuniarti, Siswari; Padoli (Gaceta Médica de Caracas, 2026)
Diabetes-related foot problems can occur and develop into diabetic foot ulcers (DFU). Correct knowledge prevents DFU and strengthens patients' self-care practices. This study aims to analyze the provision of health education through a Comprehensive Intervention Module on Foot Self-Care to increase the knowledge of patients with Diabetes Mellitus (DM) about foot self-care. This research employed a quasi-experimental design (pre-test and post-test group design with a control group). Samples were taken from 80 adults with diabetes mellitus (DM) and divided into intervention and control groups. Each group consisted of 40 adults with DM. Evaluation of the patient's knowledge using questionnaires. Data analysis using the Wilcoxon test with p<0.05 shows statistically significant values. Analysis of knowledge about foot self-care before and after module administration revealed significant differences between the intervention and control groups, with a p-value of 0.0001. Analysis of knowledge before treatment between the intervention group and the control group did not differ markedly, with p-value = 0.581. (p-value> 0.05). Analysis of knowledge after treatment revealed substantial differences between the intervention group and the control group, with a p-value of 0.0001 (p < 0.05). The mean value of knowledge after treatment in the intervention group was 89.68, which was significantly higher than the control group's 77.80. Learning through lectures and mentoring can impart knowledge more effectively than education through lectures alone. Health Education using comprehensive intervention modules on foot care can increase patients' knowledge of foot self-care. Therefore, support from health workers who can improve foot self-care behavior in DM sufferers is needed.